The tyranny of the two-party system - Disch, Lisa Jane (Power, conflict, and democracy., 2002)
Democrats and Republicans: is this duopoly an immutable and indispensable aspect of American democracy? In this text Lisa Jane Disch argues that it is not. This is an impassioned and eloquent argument in favour of third parties.